Soft Tissue Management in Facial Trauma - Braun, Tara L.; Maricevich, Renata S. (Seminars in Plastic Surgery, 2017)
The management of soft tissue injury after facial trauma poses unique challenges to the plastic surgeon, given the specialized nature of facial tissue and the aesthetic importance of the face. The general principles of trauma management and wound care are applied in all cases. The management of severe injuries to the face is discussed in relation to the location and the mechanism of injury. Facial transplants have arisen in the past decade for the management of catastrophic soft tissue defects, although high morbidity and mortality after these non-life-saving operations must be considered in patient selection.
Keywords: facial trauma; soft tissue reconstruction; facial animal bites; facial transplants